2012
DOI: 10.1155/2012/310616
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Focal Adhesions and Cancer Cell Migration

Abstract: Cells are usually surrounded by the extracellular matrix (ECM), and adhesion of the cells to the ECM is a key step in their migration through tissues. Integrins are important receptors for the ECM and form structures called focal adhesions (FAs). Formation and disassembly of FAs are regulated dynamically during cell migration. Adhesion to the ECM has been studied mainly using cells cultured on an ECM-coated substratum, where the rate of cell migration is determined by the turnover of FAs. However, the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
187
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(205 citation statements)
references
References 93 publications
8
187
1
5
Order By: Relevance
“…However, it is noteworthy that an adoption of amoeboid-based migration for non-muscle cells was not always accompanied by an increase in migration speed. It was previously proposed that rapid movement based on bleb-based migration, was partly due to the simplicity of the focal adhesions between the cells and the matrix, with less time being needed to assemble and disassemble these structures [29]. However, our results show that blebbing does not always result in increased migration, possibly due to a mis-match in the molecules needed for effective focal adhesion formation.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, it is noteworthy that an adoption of amoeboid-based migration for non-muscle cells was not always accompanied by an increase in migration speed. It was previously proposed that rapid movement based on bleb-based migration, was partly due to the simplicity of the focal adhesions between the cells and the matrix, with less time being needed to assemble and disassemble these structures [29]. However, our results show that blebbing does not always result in increased migration, possibly due to a mis-match in the molecules needed for effective focal adhesion formation.…”
Section: Discussioncontrasting
confidence: 57%
“…We suggest that non-muscle cells and satellite cells form different focal adhesions with the muscle fibre, possibly linked to their developmental history. The concept of developmental history regulating cell behaviour is well mapped in muscle, where it even segregates the properties of muscle stem cells [29]. Despite differing profiles of migration speeds, we show that the cell morphology adopted by non-muscle cells on fibres is regulated by the same molecular pathways.…”
Section: Discussionmentioning
confidence: 74%
“…3A). In summary, expression of the metastasis suppressor, NDRG1, in both cell types decreases colocalization between p-paxillin and F-actin, which are involved in focal adhesion function, including tumor cell adhesion and migration (Nagano et al, 2012).…”
Section: And B)mentioning
confidence: 89%
“…Several studies reported a transport of integrins from the rear to the front of the cell during migration, maintaining the focal adhesion turnover. The presence of large focal adhesions creates more links to actin stress fibers and makes cell movement more difficult (110). The molecular structure of FAC includes integrins, intracellularly bound to paxillin and talin, which subsequently recruit FAK and vinculin.…”
Section: Actin Rearrangement Adhesion Complexes and Cellular Protrumentioning
confidence: 99%